Mucosal-associated Invariant T-Cell Function Is Modulated by Programmed Death-1 Signaling in Patients with Active Tuberculosis - Jiang, Jing; Wang, Xinjing; An, Hongjuan; Yang, Bingfen; Cao, Zhihong; Liu, Yanhua; Su, Jinwen; Zhai, Fei; Wang, Ruo; Zhang, Guangyu; Cheng, Xiaoxing (American journal of respiratory and critical care medicine, 2014)
Mucosal-associated invariant T (MAIT) cells have been proven to play an important role in host defense against mycobacterial infection in animal infection models; however, the functional role of MAIT cells in patients with active tuberculosis (TB) is still largely unknown. To understand the clinical features and functions of MAIT cells in patients with active TB. MAIT cells were analyzed in patients with pulmonary TB, tuberculous pleurisy, and tuberculous peritonitis by flow cytometry. The functions of MAIT cells were compared between patients with active TB and healthy control subjects. The frequency of MAIT cells was significantly reduced both in peripheral blood from patients with active pulmonary TB (P < 0.0001) and in tuberculous pleural effusions compared with healthy control subjects but not in ascitic fluids from patients with tuberculous peritonitis. A comparison of bacillus Calmette-Guérin (BCG)-stimulated cytokine production showed that patients with active TB had significantly higher production of IFN-γ (P = 0.0034) and tumor necrosis factor (TNF)-α (P = 0.0399) compared with healthy control subjects. In contrast, when MAIT cells were stimulated with Escherichia coli, patients with active TB had significantly lower production of IFN-γ (P = 0.0007) and TNF-α (P = 0.0032). MAIT cells in patients with active TB exhibited elevated expression of programmed death-1 (PD-1) (P = 0.0015), and blockade of PD-1 signaling resulted in a significantly higher frequency of BCG-stimulated IFN-γ production in MAIT cells (P = 0.0178). MAIT-cell immune response to antigen stimulation in patients with active TB is regulated by PD-1, which could be a potential target for TB immunotherapy.